The Effects Of Organizational Culture On Employee Motivation – A Case Study In Vietnam - NHI, NGO TAN; SON, NGUYEN TRUONG (Journal of Ecohumanism, 2025)
Organizational culture (OC) can be considered an important motivating factor to help organizations attract and retain talent. However, there is no model that is complete, covering all aspects related to OC. This study aims to not only identify the characteristic values and constituent elements of OC in enterprises in Da Nang, but also to study the impact of OC constituent elements, including Mission, Engagement, Adaptability and Consistency, on employee motivation (EM) following the model of Denison. It has been found that the four cultural traits impacting external motivation. For internal motivation, only Engagement and Consistency have a positive impact, while Adaptation and Mission show no effect.